Analysis of Morphometric Characteristics of Indian Mackerel (Rastrelliger kanagurta Cuvier, 1816) Landed at the Fish Landing Base Tanjung Luar, East Lombok - Putri, Luh Putu Sasmita Sridewi; Karnan, Karnan; Santoso, Didik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Indian mackerel (Rastrelliger kanagurta) is a small pelagic fish species that has economic value to the community. Overfishing without management causes population decline and negative impacts on fish stocks. This study aims to analyze the morphometric characteristics of indian mackerel at Tanjung Luar Fish Landing Base (PPI), East Lombok. Data from 72 fish were collected from January to April 2024 using observation method and quantitative statistical analysis. The results of descriptive analysis showed that indian mackerel landed in Tanjung Luar PPI had average morphometric characteristics such as total length (22.07cm), standard length (18.75cm), fork length (20,35cm), head length (5.23cm), head height (4.47cm), body height (5.7cm), eye diameter (1.32cm), first dorsal fin base length (3.27cm), second dorsal fin base length (2.89cm), pectoral fin base length (2.60cm), ventral fin base length (2.35cm), anal fin base length (2.61cm), tail shaft length (4.14cm), tail shaft height (0.96cm), lower tail fin length (4.28 cm), and upper tail fin length (4.24cm). Fish growth showed an isometric growth pattern, with body parts growing proportionally. The dominant fish sizes caught were in the juvenile category at 18.2-20.6 cm (44%) and adults at 25.7-28.1 cm (28%). However, the large number of juvenile fish caught indicates the potential for overfishing, requiring effective management such as setting minimum size and fishing time to maintain the sustainability of the fish population.